PERBANDINGAN KINERJA STRUKTUR DAN BIAYA RANGKA ATAP BAJA RINGAN DAN KAYU PADA BENTANG 7 M - Rais D. Hi Yusuf (Politeknik Negeri Semarang, 2026)
Roof truss systems play an important structural role in transferring roof loads to the supporting elements of a building. The selection of roof truss materials, such as light steel and timber, affects both structural performance and construction cost. This study aims to compare the structural performance and cost of light steel and timber roof trusses with a 7 m span under identical geometry and loading conditions. The research method was conducted through structural modeling of truss systems using structural analysis, with parameters including design loads, maximum member forces, deflection, structural weight, and cost estimation. The results indicate that both roof truss systems satisfy strength and serviceability requirements. However, the light steel roof truss exhibits a smaller maximum deflection compared to the timber roof truss. In terms of structural weight, the light steel roof truss accounts for approximately 25.62% of the timber roof truss weight, resulting in a weight reduction of about 74.38%. From an economic perspective, the light steel roof truss demonstrates higher cost efficiency, with a total cost of approximately 87.47% of the timber roof truss cost. These findings suggest that, for a 7 m span, light steel roof trusses can serve as a lighter and more economical alternative to timber roof trusses while maintaining acceptable structural performance.